Rho signaling research: history, current status and future directions - Narumiya, Shuh (FEBS Lett, 2018)
One of the main research areas in biology from the mid‐1980s through the 1990s was the elucidation of signaling pathways governing cell responses. These studies brought, among other molecules, the small GTPase Rho to the epicenter. Rho signaling research has since expanded to all areas of biology and medicine. Here, we describe how Rho emerged as a key molecule governing cell morphogenesis and movement, how it was linked to actin reorganization, and how the study of Rho signaling has expanded from cultured cells to whole biological systems. We then give an overview of the current research status of Rho signaling in development, brain, cardiovascular system, immunity and cancer, and discuss the future directions of Rho signaling research, with emphasis on one Rho effector, ROCK*. *The Rho GTPase family. Rho family GTPases have now expanded to contain 20 members. Amino acid sequences of 20 Rho GTPases found in human were aligned and the phylogenetic tree was generated by ClustalW2 software (EMBL‐EBI) based on NJ algorithm. The subfamilies of the Rho GTPases are highlighted by the circle and labeled on the right side. Rho cited in this review refers to the original members of Rho subfamily, RhoA, RhoB and RhoC, that are C3 substrates, and, unless specified, not to other members of the Rho subfamily such as Rac, Cdc42, and Rnd. [Image: see text]